Discovery of 4-(3-aminopyrrolidinyl)-3-aryl-5-(benzimidazol-2-yl)-pyridines as potent and selective SST5 agonists for the treatment of congenital hyperinsulinism. (1st September 2022) - Zhao, Jian; Wang, Shimiao; Hee Kim, Sun; Han, Sangdon; Rico-Bautista, Elizabeth; Sturchler, Emmanuel; Nguyen, Julie; Tan, Hannah; Staley, Christine; Karin Kusnetzow, Ana; Betz, Stephen F.; Johns, Michael; et al.
Graphical abstract: Abstract: SST5 receptor activation potently inhibits insulin secretion from pancreatic β -cells, and an orally available nonpeptide selective SST5 agonist may be used to effectively manage the blood glucose levels of congenital HI patients to avoid severe hypoglycemia. Our medicinal chemistry efforts have led to the discovery of 4-(3-aminopyrrolidinyl)-3-aryl-5-(benzimidazol-2-yl)-pyridine analogs as potent SST5 agonists. This class of molecules exhibits excellent human SST5 potency and selectivity against SST1, SST2, SST3 and SST4 receptors. Leading compound 3-{4-[(3S)-3-aminopyrrolidin-1-yl]-5-(4-methyl-1H-1, 3-benzodiazol-2-yl)pyridin-3-yl-5-fluorobenzonitrile (28, CRN02481) showed limited off-target activity and good pharmacokinetic profiles in both male Sprague Dawley rats and Beagle dogs to advance into further preclinical evaluations.